Personal History and Physical Examination in Judgment of Urinary Tract Infection in Children Aged 3 Months to 2 Years - Po-Yu Wang; Hui-Chin Chang; Ruoh-Lih Lei; Jun-kai Kao; Chih-Lung Wu; Cheng-Han Lee; Yu-Ching Tseng; Long-Yau Lin; Ming-Sheng Lee (Elsevier, 2016)
Pediatricians ubiquitously rely on urine analysis for diagnosing urinary tract infection (UTI) in young febrile children due to discrepancies in symptom presentation. This study aimed to identify the determinants of physical examination and personal history for diagnosing UTI. Methods: Four hundred and ten patients aged between 3 months and 2 years presenting with a tympanic temperature of >38°C for >24 hours were requested to undergo urinary tests. Pediatricians completed patient record charts before the test results were generated, examined the final results of the tests, and compared the results with those reported in the medical records. Multivariate logistic regression analysis was performed to detect potential confounding factors. Results: An age of <1 year [odds ratio (OR): 5.05; p < 0.01], female sex (OR: 2.117; p < 0.05), and the absence of throat redness (OR: 1.907; p < 0.05) were risk factors for UTI. Patients defecating ≤3 times/day (OR: 8.80; p < 0.05) were more likely to have pyuria than those who defecated >3 times/day. Conclusion: For febrile patients in the age group examined, the absence of throat redness and female sex were independent predictors of UTI. Moreover, the risk of UTI was higher in younger patients.